2022
DOI: 10.1111/jog.15476
|View full text |Cite
|
Sign up to set email alerts
|

A short peptide encoded by long non‐coding RNA small nucleolar RNA host gene 6 promotes cell migration and epithelial–mesenchymal transition by activating transforming growth factor‐beta/SMAD signaling pathway in human endometrial cells

Abstract: Background Endometrial dysfunction is closely correlated with the development of multiple severe gynecological disorders including intrauterine adhesion. Accumulating evidence supports that some long non‐coding RNAs (lncRNAs) have peptide‐coding potential. In this text, the peptide‐coding ability of lncRNA SNHG6 was examined. Also, the effects of an SNHG6‐encoded peptide on the viability and migration of human endometrial stromal cells (hESCs) and human endometrial epithelial cells (hEECs) and related molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Further studies are warranted to determine whether the observed function of SNHG6 was caused by the lncRNA itself, or by its contained snoRNA. Additionally, there is recent evidence that SNHG6 encodes for a small peptide that may be functional [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are warranted to determine whether the observed function of SNHG6 was caused by the lncRNA itself, or by its contained snoRNA. Additionally, there is recent evidence that SNHG6 encodes for a small peptide that may be functional [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are warranted to determine whether the observed function of SNHG6 was caused by the lncRNA itself, or by its contained snoRNA. Additionally, there is recent evidence that SNHG6 encodes for a small peptide that may be functional [78].…”
Section: Discussionmentioning
confidence: 99%